Social security - Peterson, Jonathan (--For dummies., 2025)
"In the newly updated Social Security For Dummies, you'll find all the basics on Social Security, plus the latest updates and changes, so that you can make the most of your benefits. With clear jargon-free language and instructions, you'll figure out when to start taking your benefits, based on your unique situation and goals. This bestseller simplifies the complex Social Security system, a cornerstone of many people's retirement budgets. Social Security For Dummies will arm you with the knowledge you need to maximize your financial well-being. Get a comprehensive guide to the foundations of Social Security. Understand your benefits and prepare your long-term financial plan. Learn the latest benefits and find guidance on updated policies. Determine the best time to apply for Social Security. Whether you're gearing up for retirement, already in the Social Security groove, or helping a loved one navigate the benefits maze, this book is your golden ticket to financial peace of mind." -- Amazon